Polysome-seq as a Measure of Translational Profile from Deoxyhypusine Synthase Mutant in Saccharomyces cerevisiae - Demarqui, Fernanda Manaia [UNESP]; Paiva, Ana Carolina Silva [UNESP]; Santoni, Mariana Marchi [UNESP]; Watanabe, Tatiana Faria [UNESP]; Valentini, Sandro Roberto [UNESP]; Zanelli, Cleslei Fernando [UNESP] (Springer Nature, 2020)
The profile of proteins observed in a cell is characterized by the control of gene expression, which has several regulation points acting individually or in concert, such as epigenetic, transcriptional, translational, post-transcriptional or post-translational modification. Copulating the total mRNA data and mRNAs actively translated can facilitate the identification of the key regulatory points of gene expression. Here, we analyze the transcriptional and translational profiles of the deoxyhypusine synthase mutant dys1-1 in yeast. This enzyme is involved in the post-translational modification of translation factor eIF5A, which has an important role in the elongation translational process. This work presents gene expression data from the total mRNA levels and the polysomally-loaded mRNAs for the Saccharomyces cerevisiae DYS1 and dys1-1 strains, based on RNA-seq and Polysome-seq. Our results showed that for this mutant, most of the changes in the transcripts forwarded for translation are due to transcriptional control; and, to solve translation problems, cell responds with positive regulation of ribosome biogenesis. Besides, polysome-seq as a tool to study translation profiles is useful to understand gene expression changes.
Keywords: eIF5A; Gene regulation; Ribosome biogenesis